2022
DOI: 10.12688/wellcomeopenres.17904.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perturbed iron-homeostasis in a prospective cohort of patients with COVID-19

Abstract: Background: Marked reductions in serum iron concentrations are commonly induced during the acute phase of infection. This phenomenon, termed hypoferremia of inflammation, leads to inflammatory anemia, but could also have broader pathophysiological implications. In patients with coronavirus disease 2019 (COVID-19), hypoferremia is associated with disease severity and poorer outcomes, although there are few reported cohorts. Methods: In this study, we leverage a well characterised prospective cohort of hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…A moderate negative correlation was found between iron, Hepc, and TSAT and Hepc in the IDWA sepsis patients [ 21 ]. Our results are similar to the results in the cohort of novel coronavirus disease (COVID-19) patients in whom the negative correlation between serum iron and Hepc was weak (r = −0.24, p = 0.04) [ 25 ]. This is quite striking as an infection is known to cause hypoferremia of inflammation, which in turn leads to anemia of inflammation [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A moderate negative correlation was found between iron, Hepc, and TSAT and Hepc in the IDWA sepsis patients [ 21 ]. Our results are similar to the results in the cohort of novel coronavirus disease (COVID-19) patients in whom the negative correlation between serum iron and Hepc was weak (r = −0.24, p = 0.04) [ 25 ]. This is quite striking as an infection is known to cause hypoferremia of inflammation, which in turn leads to anemia of inflammation [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are similar to the results in the cohort of novel coronavirus disease (COVID-19) patients in whom the negative correlation between serum iron and Hepc was weak (r = −0.24, p = 0.04) [ 25 ]. This is quite striking as an infection is known to cause hypoferremia of inflammation, which in turn leads to anemia of inflammation [ 25 ]. The study by Frost et al showed that an increased inflammatory response, resulting mainly from interleukin 6 influencing the increase of hepcidin concentration, should not be associated with low serum iron.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, in severe respiratory infections such as COVID-19, profound dysregulation of the immune system drives mortality (29, 30), and intense research efforts are ongoing to establish immunerelated biomarkers for the severity and prognosis of COVID-19. These comprise both cellular (31) and humoral markers including the role of iron homeostasis (32). The objective of this study was to investigate the expression dynamics of ferritin and hepcidin as potential stratification markers in patients with septic shock or COVID-19, with emphasis on the possible immunomodulatory roles of these proteins in the context of long-term immunological exhaustion (e.g., long-term COVID-19 and post-sepsis syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…The role of hepcidin and the predictive ability of its circulating concentrations during COVID-19 and septic shock remain controversial. An analysis of biomarkers in COVID-19 patients showed that serum iron levels were strongly associated with IL-6 and other inflammatory components, but no correlation was observed with COVID-19 recovery or even hepcidin levels (32). Conversely, other groups have associated higher levels of hepcidin or iron with the severity of COVID-19 (38)(39)(40)(41) or sepsis (22), though studies in mice have reported that high hepcidin levels play a beneficial role in sepsis models (42-44).…”
mentioning
confidence: 96%
See 1 more Smart Citation